Flow over submerged energy storage balloons in closely and widely spaced floral configurations. (1st February 2015) - Vasel-Be-Hagh, A.R.; Carriveau, R.; Ting, D.S-K.
Abstract: Water flow past the accumulator unit of an underwater compressed air energy storage plant was studied numerically. The accumulator unit consists of three underwater balloons arranged in a floral configuration. The numerical simulation was conducted at a Reynolds number of 2.3 × 10 5 using URANS k–ω and LES Dyna-SM turbulence models of the ANSYS-Fluent CFD software. The URANS mean values are compatible with those of LES; however, LES appeared to better predict the turbulent nature of the studied flow. The flow pattern was illustrated through iso-surfaces of the second invariant of the velocity gradient ( Q criterion) and three-dimensional path lines. Several swirling tube flows were found to shed downstream of the balloons. The turbulence dynamic of the flow was illustrated through time-series snapshots of the vorticity contours on planes perpendicular to the flow direction; revealing the swinging movements of the observed swirling tube flows. The force coefficients of the hydrodynamic loading on these underwater structures were also investigated. The drag coefficient of the upstream balloon was found to be larger than the downstream one; the difference is more significant for the closely spaced configuration. It is noteworthy to mention that the total drag coefficient of the wide unit was larger than that of the closed one. A Fast Fourier transform of the time history of the force coefficients was used to find the Strouhal number. Strouhal numbers of approximately 0.52 and 0.18 were found for the widely spaced and closely spaced configurations respectively. Highlights: We computationally model the flow over groups of offshore energy storage balloons. Long, precessing vortex tubes are shed downstream from the balloons. Total drag coefficient of the closed case is less than that of the wide case. Total drag of floral configuration is smaller than 3 times drag of single balloon. The LES was more capable of simulating the flow turbulence than the URANS.